PENINGKATAN KETERAMPILAN BERPIKIR KREATIF MELALUI MODEL INKUIRI TERBIMBING BERORIENTASI ELEMEN PEDAGOGIS ESD (EDUCATION FOR SUSTAINABLE DEVELOPMENT) PADA SISWA SMP - Nabila Nuzul Nawafila, Sherly; Rosdiana, Laily (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to examine students’ creative thinking skills, the implementation fidelity of the learning process, and students’ responses following the application of a guided inquiry model oriented toward the pedagogical elements of Education for Sustainable Development (ESD) in renewable energy learning. This study employed a pre-experimental method with a one-group pretest–posttest design. The participants consisted of 30 ninth-grade students (class IX-D) at UPT SMPN 18 Gresik in the 2025/2026 academic year. The improvement in students’ creative thinking skills was indicated by an N-Gain score of 0.54, which falls into the moderate category. The normality test results (pretest: p = 0.001; posttest: p = 0.013) revealed that the data were not normally distributed. Furthermore, the Wilcoxon signed-rank test yielded a significance value of p = 0.000, indicating a statistically significant difference in students’ creative thinking skills before and after the intervention. The calculated effect size of 0.877 suggests a very strong practical impact of the implemented model. In addition, the implementation of the learning process achieved a mode score of 4, categorized as very good. Students’ responses reached 85%, indicating a highly positive perception of the learning experience. These findings demonstrate that the ESD-oriented guided inquiry model is effective in enhancing junior high school students’ creative thinking skills in the context of renewable energy learning